Inequality, Public Wealth, and the Federal Shareholder - Giacomo Corneo (Center for Economic Studies and ifo Institute (CESifo), 2016)
Current trends in the distribution of wealth trigger a social divide and threaten democracy. I propose to counter this evolution by enhancing the role of public capital as a redistribution and empowerment device. The governance of public capital requires two novel institutions: a socially responsible Sovereign Wealth Fund and a Federal Shareholder. This paper offers an account of their design and sources of financing.
Keywords: H00; H50; 330; public ownership; redistribution